2012
DOI: 10.1603/en11101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Development, Survival, and Fecundity ofMicroplitis manilae(Hymenoptera: Braconidae)

Abstract: Microplitis manilae Ashmead (Hymenoptera: Braconidae), a larval parasitoid, is a potential biological control agent of both Spodoptera exigua (Hübner) and Spodoptera litura (F.) (Lepidoptera: Noctuidae). Aspects of the climatic requirements for development, including survival, longevity, and fecundity of M. manilae were studied at six constant temperature regimes (17, 20, 23, 26, 29, and 32°C) in the laboratory. The results showed that developmental duration for egg, larva, pupa, and the entire immature stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
3
26
0
1
Order By: Relevance
“…Low L. invasa adult survival at higher temperatures was similar to that observed for Microplitis manilae (Hymenoptera: Braconidae) ( Qiu et al, 2012 ). Increased survival at low temperatures can be associated with reduced activity and metabolism ( Bleicher & Parra, 1990 ) and low females survival at higher temperatures may be due to metabolic increases or enzyme destruction at higher temperatures ( Mohan, Verma & Singh, 1992 ).…”
Section: Discussionsupporting
confidence: 75%
“…Low L. invasa adult survival at higher temperatures was similar to that observed for Microplitis manilae (Hymenoptera: Braconidae) ( Qiu et al, 2012 ). Increased survival at low temperatures can be associated with reduced activity and metabolism ( Bleicher & Parra, 1990 ) and low females survival at higher temperatures may be due to metabolic increases or enzyme destruction at higher temperatures ( Mohan, Verma & Singh, 1992 ).…”
Section: Discussionsupporting
confidence: 75%
“…Of all the climatic variables, temperature is perhaps the most influential on insect distribution, reproduction, development, and survival (Baffoe et al, 2012;Bale et al, 2002;Ju et al, 2011;Infante 2000). Thus, identifying which temperatures favor rapid population growth is important not only for optimizing release strategies (Pilkington and Hoddle, 2006a), but this knowledge is critical for mass-rearing programs that aim to produce the most quality (fittest) biological control agents in the shortest time frames (Qiu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the duration of the egg stage may be the principal factor determining the success of a parasitoid in intrinsic competition because the first-hatching species can use the host's resources immediately and attack the eggs of the other parasitoids (Tillman & Powell, 1992;Bajpai et al, 2006;Tian et al, 2008). Qiu et al (2012) reported that the eggs of S. manilae hatched in approximately 2.7 days (26°C, LD 14:10 h) when second-instar Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae) was the host. When M. pulchricornis was observed to parasitize Mythimna separata (Walker) (Lepidoptera: Noctuidae), the egg period was approximately 3.8 days (25 ± 1°C, LD 16:8 h) (Magdaraog et al, 2012).…”
Section: Discussionmentioning
confidence: 99%